Variability and inheritance of okra leaf- shape of cotton cv. Sudac-k in different genetic backgrounds - Abd alla, Nazik A.; Ali, Abdelbagi M.; Ibrahim, Abu Elhassan S. (Gezira Journal of Agricultural Science, 2017)
Okra leaf- shape is an important trait in cotton. Sudac-k is the only cotton variety with okra leaf type in the Sudan. The objectives of the study were to analyze the inheritance of the okra leaf of Sudac-k and its expression in different genetic backgrounds. The experiment was carried out for two seasons (2004/05 and 2005/06) and one off-season in 2006 at Gezira Research Farm of the Agricultural Research Corporation (ARC), Wad Medani, Sudan. The plant material consisted of Sudac-k and nine different varieties; B-pima, Barakat-90, G.S, Maryoud, Shambat-B, Acala-M, Acala-H, Barac (67) B and Albar (57)12. Eighteen reciprocal F 1 s were produced between Sudac-k and respective cultivars. In the second season, F 2 ҆s, backcrosses and F 3 plants were (Sudac-k X Albar (57)12). At maturity, individual plants were visually scored according to the leaf-shape into okra and normal leaf shape. Okra leaf morphology, lobe length, width and angle were measured in fully expanded 5- lobed leaf. It was observed that the okra leaf of Sudac-k had deep sinuses and narrow lobes while in F 1 ҆ s, the sinuses were shorter and the lobes were broader. The okra leaf started at seedling stage with three lobes at the 3rd to 4th node and reached a maximum of 5 lobes at node 6 to 8 in Sudac-k, F 1 plants and their progenies. Chi-square test for the segregation of leaf type in F 2 indicated no significant differences among all F 1 ҆ s between Sudac-k and the varieties in the distribution of okra and normal which followed the ratio of 1:2:1. This indicates that the okra leaf trait is conditioned by a single partially dominant gene. Significant differences were observed among the F 1 hybrids for the expression of leaf lobing depth, lobe width and angle, indicating the effect of the genetic background on the expression of these parameters. The information will be useful in designing strategy for breeding of cotton varieties with suitable size of okra leaf to maximize its utilization in integrated insect pest management.